THE STUDENTS' PERSPECTIVE IN STUDYING REPORT TEXT THROUGH BRITISH COUNCIL LISTENING AUDIO - Ardiansyah, Muhammad Rizal (ELite Journal : International Journal of Education, Language and Literature, 2024)
In the globalization era, the used of Technology Pedagogical Content Knowledge (TPACK) is a fundamental aspect in English Language Teaching (ELT). The British Council Web is a broad online platform with educational resources, language study materials, and cultural content. It is a wonderful resource for people all over the world who want to improve their language abilities, learn about British culture, and get access to high-quality educational materials. British Council web also provided kinds of audio as authentic listening materials. This study investigates the students' perspective in studying report text through British Council listening audio. The descriptive qualitative method was used in this research. The learners of SMP Negeri 36 Semarang in 9G grade are the focus of this research. The participants were given a questionnaire consisted of two indicators namely perceived excitement and perceived easy to use and usefulness. The first indicator shows 81,87%, it is in very high grade interval. Then, for the second indicator: perceived easy to use and usefulness is in 80,13%. It is also in very high grading interval. The average of two indicators calculated 81% is in very high grade interval. It means that the students have positive perspective in using British Council audio.